Correction of Vitamin D Deficiency and its Effects on Immunologic and Metabolic Disorders in Young Children Who Often Suffer from Respiratory Diseases - T.V. Pochynok (Zaslavsky O.Yu., 2016)
This article deals with the problem of vitamin D deficiency and problem of its correction. The findings of the study on vitamin D sufficiency in infants by determining 25(OH)D3 levels in venous blood are presented, recommendations for the administration of oily solution of vitamin D (Vigantol) are given.